Pengaruh penerapan LKS virtual laboratory dengan model pembelajaran cooperative type group investigation terhadap kompetensi belajar fisika siswa kelas X MIA SMA Adabiah Padang - Radha Firaina; masril masril; hidayati hidayati; yenni darvina (Universitas Negeri Padang, 2019)
Improving the quality and competitiveness of Indonesia's resources has become a national commitment. One of the government's efforts to provide Information and Communication Technology (ICT) in schools is expected to be able to support the improvement of school students' competency achievement. But in reality, in physics learning the achievement of all aspects of student competence is still not optimal. One of the main causes is the lack of optimal use of student worksheet and practical activities due to incomplete laboratory equipment. The solution that can be done is to do practicum virtually. The purpose of this study was to determine the effect of Virtual Laboratory Student Worksheets with Cooperative Type Group Investigation Learning Model on Class X Physics Learning Competencies. The population of this study was students of class X MIA SMA Adabiah Padang and two classes were selected by cluster random sampling technique. Students were divided into experimental groups and control groups. The assessment instrument used for attitude competency is the observation sheet, for knowledge competency is a multiple choice test, and for skills competency using performance sheets. The results of the attitude competency assessment in the form of descriptions through comparison charts between the two conditions tended to increase during the seven meetings for each aspect. Effects of the Virtual Laboratory worksheet on the achievement of students' Physics competencies in skills competency by 20.66% and knowledge competencies by 34.44%, others are influenced by other factors. Based on the results of the research obtained, it can be concluded that there is an effect which means the use of virtual laboratory student worksheet on attaining competency attitudes, knowledge and skills of students in physics learning class SMA Adabiah Padang.